Wintertime controls on summer stratification and productivity at the western Antarctic Peninsula. (5th May 2013) - Venables, Hugh J.; Clarke, Andrew; Meredith, Michael P.
Abstract : We report results collected year‐round since 1998 in northern Marguerite Bay, just inside the Antarctic Circle. The magnitude of the spring phytoplankton bloom is much reduced following winters with reduced sea‐ice cover. In years with little winter sea‐ice the exposed sea surface leads to deep mixed layers in winter, and reduced water‐column stratification the following spring. Summer mixed‐layer depths are similar, however, so the change is not in overall light availability but toward a less stable water column with greater vertical mixing and increased variability in the light conditions experienced by phytoplankton. Macronutrient concentrations are replete at all times, but the increased vertical mixing likely reduces iron availability. The timing of bloom initiation is similar between heavy and light ice years, occurring soon after light returns in early spring, at a mixed‐layer averaged light level of < 1 mol photon m −2 d −1 . Ongoing regional climate change in the WAP area, and notably the ongoing loss of winter sea‐ice, is likely to drive a downward trend in the magnitude of phytoplankton blooms in this region of the Antarctic Peninsula.